1960 Commencement, Dr. Emory Morris - Julian A. McPhee:::::::::; Emory Morris::::::::: (1960)
[00:00:03] Julian McPhee discusses the work of the W. K. Kellog Foundation toward the advancement of material and ideological gains in the world [00:00:42] McPhee states that it was the Kellog Foundation that donated a horse ranch to Cal Poly in 1949 [00:01:16] McPhee talks about the role of Dr. Morris in facilitating the gift from the Kellog Foundation [00:01:51] McPhee lists the professional and educational credentials of Dr. Morris [00:02:28] McPhee introduces the President of the W. K. Kellog Foundation as the commencement speaker, Dr. Emory Morris [00:03:17] Morris talks about the memories that remain from the college experience [00:04:03] Morris says that education is the vital undergirding of modern society [00:04:37] Morris states he has long admired the teaching philosophy of Julian A. McPhee [00:05:25] Morris says he believes that modern education is improving at providing richer, fuller lives of individuals and their communities [00:06:10] Morris tells a story about a man whose vision was only focused on small things on the ground, gaining money but losing the joy of friends and nature [00:07:58] Morris talks about George Berkeley the Irish philosopher and his famous line, 'Westward, the course of empire takes its way' [00:08:37] Morris talks about all of the people that helped to build California [00:09:27] Morris talks about the progress of industrial economy based on individual specialization, but that humans remain social creatures [00:10:19] Morris says that perhaps it is inevitable that man finds satisfactions within a variety of groups, but it is important that we must learn to live away from the group just as we live in it [00:10:51] Morris notes the level of conformity traded for convenience and comfort [00:11:40] Morris affirms that the educated man must walk the tightrope between anarchy and conformity [00:13:04] Morris states that he recently read Eric Prone's Escape to Freedom, but thought 'freedom for what?' [00:13:30] Morris pauses for a train passing by [00:14:42] Morris says it is the job of education to decide what to use for freedom [00:15:25] Morris says the educated man is obligated to act in a noble and decisive manner [00:16:24] Morris quotes from Ian Foster's Two Chairs for Democracy [00:17:58] Morris talks about Alfred Nobel, the Swedish industrialist and inventor of dynamite, which he saw as a benefactor of mankind but his invention was perverted by the munitions industry for killing [00:19:01] Morris continues telling the story of Nobel seeing how the world viewed him through newspapers incorrectly reporting his death and obituaries [00:20:25] Morris calls upon the duty of educated citizens to mitigate the social waste of the average community [00:20:54] Morris tells a story about community integrity in which a boy threw a rock through a barbershop window, leading to members from the community supporting the barbershop whether they needed to or not [00:21:40] Morris quotes Confucius on wisdom, compassion, personal conduct, and governance [00:23:11] Morris reiterates that a truly educated person represents the chief basis of optimism going into the future [00:24:12] Morris ends his speech